2019
DOI: 10.1155/2019/5432453
|View full text |Cite
|
Sign up to set email alerts
|

Urine 5MedC, a Marker of DNA Methylation, in the Progression of Chronic Kidney Disease

Abstract: Background. Alterations in DNA methylation may be involved in disease progression in patients with chronic kidney disease (CKD). Recent studies have suggested that 5-methyl-2′-deoxycytidine (5MedC) may be a marker of hypermethylation of DNA. Currently, there is no information available regarding the urine levels of 5MedC and its association with the progression of CKD. Method. We examined the urine levels of 5MedC in spot urine samples from 308 patients with CKD (median age: 56 years, male: 53.2%, and glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…In the present study, we observed that increased levels of 5mdC (%), a global DNA methylation indicator, were associated with decreased eGFR, and also CKD cases compared to controls had higher odds of having elevated 5mdC levels. This is consistent with a Japanese prospective study that recruited 308 CKD patients (43), which showed that concentrations of 5mdC (measured in urine specimens) were significantly higher among late-stage compared to early-to mid-stages patients, and increased 5mdC levels were associated with low eGFR (<30 mL/min/1.73m 2 ; OR = 2.36, 95%CI: 1.24-4.60) in the multivariable adjusted model. However, in a cross-sectional study of 78 kidney disease patients among stages 2-4 conducted in the Netherlands (44), no differences were found between the levels of global DNA methylation (measured by the ratio of 5-methylcytosine and total cytosine ratio in the blood specimens) and kidney disease stages.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we observed that increased levels of 5mdC (%), a global DNA methylation indicator, were associated with decreased eGFR, and also CKD cases compared to controls had higher odds of having elevated 5mdC levels. This is consistent with a Japanese prospective study that recruited 308 CKD patients (43), which showed that concentrations of 5mdC (measured in urine specimens) were significantly higher among late-stage compared to early-to mid-stages patients, and increased 5mdC levels were associated with low eGFR (<30 mL/min/1.73m 2 ; OR = 2.36, 95%CI: 1.24-4.60) in the multivariable adjusted model. However, in a cross-sectional study of 78 kidney disease patients among stages 2-4 conducted in the Netherlands (44), no differences were found between the levels of global DNA methylation (measured by the ratio of 5-methylcytosine and total cytosine ratio in the blood specimens) and kidney disease stages.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, information on disease captured via methylation markers in blood or urine could be used as a non-invasive screening tool to follow disease progression and severity in CKD. Recently, it has been shown that urinary methylation levels were able to predict a 30% decline in the estimated GFR, or development of KF over a period of three years, when combined with macroalbuminuria or an increased level of Alpha 1 Microglobulin 95 . Finally, data showing that cholesterol lowering treatment restores blood DNA methylation in patients with CKD stages 3–4 suggest that methylation could also be a functional and relevant measurement of treatment response 96 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on biomarkers for the diagnosis of T2D have not been validated in a clinical environment. Instead, the researchers have been more interested in developing biomarkers for one specific comorbidity, kidney disease ( Table 9 ) [ 173 , 174 , 175 ]. Because urine examinations identify changes in gene expression in urine-derived cells [ 176 ], they may be helpful for the noninvasive assessment of kidney condition and prediction in early T2D [ 177 ].…”
Section: Epigenomics Biomarkers For T2dmentioning
confidence: 99%